ALTERNATIF PENGELOLA WISATA PANTAI HALASSY NEGERI MORELLA KABUPATEN MALUKU TENGAH PADA FASE PRA DAN PASCA-KRISIS COVID-19 - Eygner Gerald Talakua; Renoldy Lamberthy Papilaya; Willem Talakua; Eli Serravallo Lewerissa (Universitas Pattimura, 2021)
The involvement of related parties is needed in determining the right alternative to manage Halassy Beach Tourism, Morella Village, Central Maluku Regency. The purpose of this study was to determine the role of the government, private sector, and community in managing and determining the appropriate alternative managers in the pre and post crisis phases of covid-19. Through the purposive sampling method, 20 respondents were obtained from experts or stakeholders in the field of tourism and the economics of fisheries and marine resources. Primary data collection was conducted by interview using a google form questionnaire. Descriptive method is used to describe the general condition of the study area, the characteristics of the respondents, as well as the role of the government, private sector and community. Data analysis used analytical hierarchy process (AHP).The results show that in the pre covid-19 crisis phase, the government can build tourist areas that are environmentally and culturally aware; the community as managers are able to improve the information access for tourists; and the private sector contributes economic and social benefits to management capacity. In the post covid-19 crisis, the government needs to pay attention to tourism potential that can be developed; the community can apply the 4A concept; and the private sector can create more interesting ideas to bring in tourists. The right alternative for Halassy Beach Tourism management in the pre and post-covid-19 crisis phases is collaboration between the community, government and private sector, in the triple helix concept.